HUBUNGAN MOTIVASI TERHADAP TINGKAT AKTIVITAS FISIK SISWA EKSTRAKURIKULER OLAHRAGA DI SMA NEGERI 16 PEKANBARU - Mhd. Anugerah Rafiyansyah; Aref Vai; Agus Prima Aspa; Aidil Syaputra; Kristi Agust; Purwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Motivation is considered one of the factors influencing students' physical activity in school sports extracurricular programs. This study aimed to examine the relationship between motivation and physical activity levels among students participating in sports extracurricular activities at SMA Negeri 16 Pekanbaru. A quantitative correlational design was employed using total sampling involving all active extracurricular sports participants. Motivation data were collected using a Likert-scale questionnaire adapted from Melinda (2024), while physical activity was measured using the International Physical Activity Questionnaire-Short Form (IPAQ-SF). Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and Spearman Rank correlation with SPSS. The findings indicated that students' motivation ranged from moderate to high, while their physical activity level was generally high. Spearman Rank analysis revealed a significant positive correlation between motivation and physical activity (r = 0.306; p = 0.019), although the correlation strength was low. These findings suggest that motivation contributes to students' physical activity but is not the sole determinant. Other factors, including daily activities, environmental conditions, and the availability of sports facilities, also influence students' physical activity levels. The results provide useful information for schools in developing strategies to improve students' motivation and participation in sports extracurricular activities.